Nursing of a patient with low back pain of Qi-stagnation and blood stasis syndrome treated by Bian-stone hot ironing-massage and Chinese herbal medicine penetration (砭石熨摩中药透入法治疗气滞血瘀型腰痛1例的护理体会) - ZHANG Xuelian (张雪莲); GUO Huanli (郭换利); ZHAO Jing (赵静) (中西医结合护理)
This paper summarized the nursing management of a patient with low back pain of Qi-stagnation and blood stasis syndrome treated by Bian-stone hot ironing-massage and Chinese herbal medicine penetration. In addition to the routine nursing and health education, the combination of Bian-stone hot ironing-massage and Chinese herbal medicine penetration were carried out based on the clinical symptoms evaluation and syndrome differentiation. Bian-stone hot ironing-massage combined with Chinese herbal medicine penetration is effective to relieve the symptoms of low back pain and improve the activity of daily living. (本文总结1例砭石熨摩中药透入法治疗气滞血瘀型腰痛的护理体会。根据患者腰部疼痛以及辨证分型, 在生活起居管理、健康宣教等常规护理基础上, 实施砭石熨摩中药透入法疗法, 明显改善患者腰部疼痛的症状, 日常生活能力明显提高。)